Wake interaction in offshore wind farms with mesoscale derived inflow condition and sea waves. Issue 1 (1st September 2022) - Castorrini, A.; Tieghi, L.; Barnabei, V.F.; Gentile, S.; Bonfiglioli, A.; Corsini, A.; Rispoli, F.
Abstract: Numerical simulation is an indispensable tool for the design and optimization of wind farms layout and control strategies for energy loss reduction. Achieving consistent simulation results is strongly related to the definition of reliable weather and sea conditions, as well as the use of accurate computational fluid dynamics (CFD) models for the simulation of the wind turbines and wakes. Thus, we present a case study aiming to evaluate the wake-rotor interaction between offshore multi-MW wind turbines modelled using the Actuator Line Model (ALM) and realistic wind inflow conditions. In particular, the interaction between two DTU10 wind turbines is studied for two orientations of the upstream turbine rotor, simulating the use of a yaw-based wake control strategy. Realistic wind inflow conditions are obtained using a multi-scale approach, where the wind field is firstly computed using mesoscale numerical weather prediction (NWP). Then, the mesoscale vertical wind profile is used to define the wind velocity and turbulence boundary conditions for the high-fidelity CFD simulations. Sea waves motion is also imposed using a dynamic mesh approach to investigate the interaction between sea waves, surface boundary layer, and wind turbine wakes and loads.